Tropical diabetic hand syndrome in a Solomons Islands adult: A case report of a rare complication. (April 2023) - Bush, Dylan; Natuzzi, Eileen; Koburu, Gordon; Bana, Maggie; Taki, Flins; Melly, Augustin
Abstract: Background: Tropical diabetic hand syndrome (TDHS) is a rare and often unrecognized complication that can lead to lifelong disability or even death among diabetic patients living in the tropics. Presentation of case: This study reports the case of a 47-year-old male patient in the Solomon Islands who developed TDHS caused by Klebsiella pneumonia . The patient presented with symptoms of localized cellulitis of the fourth digit of the left hand after being discharged 10.5 weeks prior for an infection on the second digit of the left hand. Subsequent physical exams, surgical debridement, and patient monitoring indicated that the cellulitis spread and developed into necrotizing fasciitis. Despite serial surgical debridement and a fasciotomy, as well as administration of antidiabetic agents and antibiotics, the patient developed sepsis and died forty-five days post-admission. Discussion: Medication shortages, late presentation, and failure to pursue aggressive surgery increases risk of TDHS patient morbidity and mortality. Conclusion: TDHS requires early detection and presentation, aggressive surgical management, and efficient administration of antidiabetic agents and intravenous antibiotics. Highlights: Tropical diabetic hand syndrome (TDHS) is a rare acute condition affecting diabetic patients living in the tropics. Early identification, aggressive surgical intervention, and early administration of broad spectrum IV antibiotics are key. Limited resource settings pose various challenges to the effective management of infection and TDHS. Access to medications, diagnostic equipment, and knowledge about identifying and treating TDHS may help reduce mortality.